2018
DOI: 10.1063/1.5031001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluorine incorporation into β-Ga2O3

Abstract: β-Ga2O3 rectifiers fabricated on lightly doped epitaxial layers on bulk substrates were exposed to CF4 plasmas. This produced a significant decrease in Schottky barrier height relative to unexposed control diodes (0.68 eV compared to 1.22 eV) and degradation in ideality factor (2.95 versus 1.01 for the control diodes). High levels of F (>1022 cm−3) were detected in the near-surface region by Secondary Ion Mass Spectrometry. The diffusion of fluorine into the Ga2O3 was thermally activated with an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…). 308,309 The experimental results about the surface of Ga 2 O 3 absorbed by the different impurities showed that different surface treatments had different effects on the electronic properties ( e.g. , Schottky barrier height, etc .)…”
Section: Effects Of Defects and Impurities On Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…). 308,309 The experimental results about the surface of Ga 2 O 3 absorbed by the different impurities showed that different surface treatments had different effects on the electronic properties ( e.g. , Schottky barrier height, etc .)…”
Section: Effects Of Defects and Impurities On Electronic Propertiesmentioning
confidence: 99%
“…For example, Yang et al investigated the bulk Ga 2 O 3 materials after surface treatment such as plasma treatment (CF 4 and O 2 ), gaseous treatment (ultraviolet/O 3 ), and liquid treatment (HCl, H 2 O 2 , etc.). 308,309 The experimental results about the surface of Ga 2 O 3 absorbed by the different impurities showed that different surface treatments had different effects on the electronic properties (e.g., Schottky barrier height, etc.) of bulk Ga 2 O 3 .…”
Section: Mgmentioning
confidence: 99%
“…24) TLM measurements on the regrown n + layer without any channel layer, showed a ρ c ∼ 10 −6 Ω cm 2 indicating low resistance n + Ga 2 O 3 /Ti contact. The high R c is attributed to etch damage and charge depletion due to fluorine ions 31) resulting from the SF 6 /Ar dry etch step used before the contact regrowth step. Switching to BCl 3 /Ar chemistry-based dry etch step could lead to lower contact resistivity.…”
mentioning
confidence: 99%
“…23 However, it is not widely appreciated that the surface of β-Ga 2 O 3 can be strongly affected by exposure to gaseous or plasma environments and the influence of changing conductivity and roles of surface states in oxidizing or reducing environments are not well-established. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] This is despite the fact that Ga 2 O 3 rectifiers are known to be sensitive detectors of hydrogen. 25,26 The (−201) Ga 2 O 3 surface has been reported to be particularly sensitive to plasma-induced damage, leading to device performance degradation.…”
mentioning
confidence: 99%
“…This work complements previous studies where the Ga 2 O 3 was exposed to these plasmas in immersive mode, where combined chemical and physical bombardment effects are present. 24,28,29…”
mentioning
confidence: 99%